PERBANDINGAN BOQ TULANGAN ANTARA METODE KONVENSIONAL DENGAN BIM APARTEMEN “X” - Tasya Putri Artanti; I Ketut Sucita; Erlina Yanuarini (Politeknik Negeri Jakarta, 2022)
When modeling buildings and calculating quantity, changes in the drawings often result in changes to the calculation quantity. Calculations Quantity using conventional methods still uses the area or volume formula to get the volume of work. The volume of work calculated using conventional methods is sometimes inaccurate because it often uses assumptions in its calculations. In this case, it is necessary to develop information technology that integrates modeling and calculations quantity. Building Information Modeling (BIM) is a technology that can model buildings and provide information such as the quantity of the building modeling results. The BIM method is entirely accurate in planning calculations and is expected to solve the problems that exist in conventional methods. This study aims to compare the Bill of Quantity of reinforcement using the conventional method and the BIM method where the author uses an analytical method with the help of Tekla Structures Software. Based on the research conducted, the percentage difference in Bill of Quantity using the BIM method has an average volume of 1.95% greater than the conventional method. This difference is due to an error when inputting data (human error) and is less accurate, such as not calculating the radius or bending of the reinforcement.